Chemical analysis of rainfall and throughfall in the Tapajós National Forest, Belterra, Pará, Brazil - Raimundo Cosme de Oliveira Junior (Revista Ambiente & Água, 2015)
The Tapajós National Forest (FLONA Tapajós) has 600,000 hectares of protected forest, and is situated 50 km south of the city of Santarém, Pará, Brazil, a port city of 250,000 inhabitants that is located at the confluence of the Tapajós and Amazon Rivers. There is a lot of farmland in the region, which offers many opportunities to study changes in land use. Selective wood harvesting is one type of land use that is particularly important to the economy of Santarém. Wet and dry deposition of organic material can be an important source of nutrients for plants, and this is especially true when the soil is poor, which is the case in Santarém-Belterra plateau region, the study area of this research. In this region, the natural atmospheric deposition of nutrients is often enhanced by the burning of biomass, which releases a large part of the above-ground biomass nutrients into the atmosphere. The objectives of this study were: 1 - estimate the total wet deposition via direct precipitation and through the canopy, including dry deposition; 2 - verify potential sources of nutrients found in the total wet deposition and dry deposition; and 3 - investigate the effects of coverage vegetation on nutrient content in precipitation and throughfall. The study was conducted in FLONA Tapajós at km 67 of Santarém- Cuiabá Highway, south of the city of Santarém. The study area consisted of a portion of 100 x 100 m transects divided into 10 x 10 m plots. The area was located next to a meteorological tower 65 m tall that measures various climate parameters such as rainfall, wind speed and direction, solar radiation, temperature and humidity, among others. Direct precipitation (PD) and internal precipitation (IP) collectors consisted of 2 L polyethylene bottles with a 115 mm diameter funnel. Samples were collected weekly from April 2003 to March 2006. The volume of the sample was measured individually for each collector (25 traps for internal precipitation and 4 for direct precipitation). The conclusions that can be drawn from this study are: 1 - the dry season has the highest variation in ion flux; 2 - seasonality has a strong influence on the concentration of basic cations; 3 - dry deposition is one of the most important ways that nutrients are acquired in FLONA Tapajos; 4 - there is a significant inflow of nutrients Cl and Na due to intensive grain farming nearby; 5 dry deposition is the most important process for the enrichment of water that reaches the forest floor; 6 - principal component analysis facilitates the interpretation and characterization of rainwater and in this study shows the influence of anthropogenic sources such as agriculture, biomass burning, and dust.